EFL Teachers’ and Students’ Gestures: N-VC Strategy in an Online Classroom - Rusdiah; Muhammad Aswad; Nurdina Rasjid (IAI DDI POLEWALI MANDAR, 2024)
This study aimed to explore the teacher’ and students’ gestures, and the function of the gestures in an online EFL classroom. The researcher applied a qualitative research design. The subject of research was 9 students, 2 teachers in the English Department, and an expert in expression. The research instruments were passive participant observation, interview, and documentation. The result of the research revealed that both the teachers and students used gestures. Teachers applied speech-independent and speech-related gestures. The speech-relate gestures were clenching, pointing, and raising hands. In contrast, the speech-independent gestures were nodding with nothing to do with what she was explaining. However, students’ gestures were often invisible on the screen due to the constraints of limited screenshots. The function of gestures was to substitute words and instruction. Additionally being mindful of their gestures can send mixed signals or unintentionally convey negative emotions or attitudes. So, all teachers must consciously use gestures to support their message. The study’s novelty lies in its focus on the online EFL classroom context, a relatively unexplored area in the field of language education research. By examining the specific strategies used in an online setting, this study provides new insights into the role of N-VC in virtual learning environments. This is particularly relevant given the increasing reliance on online education due to recent global events, making the findings timely and applicable.